Penggunaan Media Digital Interaktif Dalam Pembelajaran Sejarah Di Sekolah Menengah - Aliyah (Jurnal Sains, Teknik, Ekonomi, dan Pendidikan, 2025)
History education in high school often faces the challenge of low student learning interest in the digital era. This research aims to conduct an in-depth examination of the use, impact, and implementation challenges of interactive digital media in history learning. Using a qualitative approach with a case study design at a public high school in Medan, data were collected through classroom observations, in-depth interviews with teachers, and Focus Group Discussions (FGDs) with students. The findings indicate that the use of interactive digital media significantly increases students' enthusiasm, active participation, and understanding of the subject matter. This media proved effective in facilitating the development of historical empathy and critical thinking skills. However, the study also identified several challenges, including an increased teacher workload in preparing materials, the need for proficient pedagogical-technological competence, and technical infrastructure constraints at the school. In conclusion, interactive digital media is a powerful pedagogical tool for revitalizing history education, but its effectiveness is highly dependent on a well-planned implementation strategy, teacher readiness, and adequate institutional support.